Randomized shortest paths for Grizzly Bear dispersal between the GYE and NCDE - Christopher P. Peck; Frank T. van Manen; Cecily M. Costello; Mark A. Haroldson; Lisa A. Landenburger; Lori L. Roberts; Daniel D. Bjornlie; Richard D. Mace (USGS Science Data Catalog, 2017)
The Randomized Shortest Path (RSP) raster delineates potential dispersal paths for male-mediated gene flow between grizzly bear (Ursus arctos) populations in the Greater Yellowstone Ecosystem (GYE) and the Northern Continental Divide Ecosystem (NCDE). A RSP algorithm was used to estimate the average number of net passages for all grid cells at a spatial resolution of 300 m in the study region which spans parts of Montana, Idaho, and Wyoming. RSP rasters identify potential movement paths for 3 levels of random deviation determined by the parameter Θ (i.e., Θ = 0.01, 0.001, and 0.0001) for bears moving from an origin to a destination node. Lower values of Θ result in greater exploration and more random deviation around the shortest path (Θ = 0 equivalent to pure random walk), whereas larger values approach the equivalent of a least-cost path. Broad-scale concordance between model predictions was found for paths originating in the NCDE and those originating in the GYE for all 3 levels of movement exploration. The resulting RSP rasters provide evidence that landscape features concentrate movement paths into corridors (e.g., because of anthropogenic influence), and delineate paths that typically follow neighboring mountain ranges. Movement paths that converge at junctions between several ranges may serve as pivotal stepping stones for grizzly bear movement and successful dispersal.